2013
DOI: 10.12957/demetra.2013.6210
|View full text |Cite
|
Sign up to set email alerts
|

Desafios À Reforma Curricular Em Um Curso De Graduação Em Nutrição: Relato De Experiência

Abstract: Challenges to the curricular reform in a nutrition undergraduate courseResumo Estudo longitudinal, descritivo, com o objetivo de identificar os desafios persistentes à reforma curricular do curso de graduação em Nutrição da Universidade Federal Fluminense, comparando avaliações docentes das disciplinas realizadas em 2009 e 2011. Coletaram-se dados através de questionário com nove questões mistas seguindo orientação do Projeto Pedagógico do Curso. Participaram 23 professores em 2009 e 34 em 2011. Selecionaram-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…In December 2018, the 709 existing Undergraduate Courses in Nutrition were distributed among the 27 states of the Federation [19], with a slight change occurring among the ten largest concentrations per state: São Paulo (158 courses or 22.3% of the total number), Rio de Janeiro (76 or 10.7%), Minas Gerais (71 or 10.0), Bahia (59 or 8.3%), Rio Grande do Sul (37 or 5.2%), Paraná (34 or 4.8%), Pernambuco (31 or 4.4%), Ceará (25 or 3.5%), Santa Catarina (24 or 3.5%) and Goiás (20 or 2.8%) ( Table 2). Table 2, the ten states where the highest absolute increases occurred in the number of attendance courses of Nutrition Graduation between August 2009 and December 2018 were: São Paulo (50), Rio de Janeiro (43), Bahia (40), Pernambuco (23), Ceará (20), Rio Grande do Sul (16), Mato Grosso (12), Santa Catarina and Paraíba (11), Distrito Federal, Maranhão, Pará and Sergipe (10). In terms of relative increases, the ten states that verified the highest results were: In 2009, 56.5% of the Nutrition Courses were concentrated in the Southeast Region of Brazil [3], which remained the region with the highest number of courses in 2018, with 44.6% of the total.…”
Section: The Evolution In the Number Of Face-to-face Undergraduate Comentioning
confidence: 99%
See 2 more Smart Citations
“…In December 2018, the 709 existing Undergraduate Courses in Nutrition were distributed among the 27 states of the Federation [19], with a slight change occurring among the ten largest concentrations per state: São Paulo (158 courses or 22.3% of the total number), Rio de Janeiro (76 or 10.7%), Minas Gerais (71 or 10.0), Bahia (59 or 8.3%), Rio Grande do Sul (37 or 5.2%), Paraná (34 or 4.8%), Pernambuco (31 or 4.4%), Ceará (25 or 3.5%), Santa Catarina (24 or 3.5%) and Goiás (20 or 2.8%) ( Table 2). Table 2, the ten states where the highest absolute increases occurred in the number of attendance courses of Nutrition Graduation between August 2009 and December 2018 were: São Paulo (50), Rio de Janeiro (43), Bahia (40), Pernambuco (23), Ceará (20), Rio Grande do Sul (16), Mato Grosso (12), Santa Catarina and Paraíba (11), Distrito Federal, Maranhão, Pará and Sergipe (10). In terms of relative increases, the ten states that verified the highest results were: In 2009, 56.5% of the Nutrition Courses were concentrated in the Southeast Region of Brazil [3], which remained the region with the highest number of courses in 2018, with 44.6% of the total.…”
Section: The Evolution In the Number Of Face-to-face Undergraduate Comentioning
confidence: 99%
“…On the one hand, there was a great expansion in the number of courses, on the other, the LDB, the Health Reform and the National Health Conferences provided support for training projects committed to a comprehensive and universal assistance, as proposed by the SUS guidelines [11,13]. In turn, the Diretrizes Curriculares Nacionais (DCN, National Curricular Guidelines) in 2001 established provisions in the direction of strengthening training in defining the profile of the nutritionist and ratifying the social needs in the health field and the emphasis on SUS, as the guiding axis of the Projetos Pedagógicos dos Cursos (PPC, Pedagogical Projects of Courses) [12][13][14][15]20]. In the last three decades, it has been observed that private sector growth was maintained, not being reversed after 2003, when there was a relative increase in vacancies in public universities [3].…”
Section: Still According Tomentioning
confidence: 99%
See 1 more Smart Citation
“…In this systematic review, a Brazilian study highlighted the high number of research projects carried out on Public Health [23], a fact that, according to Costa et al [39], contributes to addressing local problems and transforming knowledge into concrete actions. However, some studies emphasize the presence of the research-teaching dichotomy in formal education, and the lecturers were predominantly focused on research activities, overlooking teaching [39][40][41].…”
Section: Checklist For Qualitative Researchmentioning
confidence: 99%
“…O Brasil atual passa por um processo semelhante (Costa et al, 2013. Garcia e Silva, 2010Vieira e Tamousauskas, 2013).…”
Section: Avaliação Do Ensino Pelos Alunosunclassified